EFL students’ language attitudes toward virtual learning environment: A technology acceptance model - Faiqoh, Avita Elok; Ashadi, Ashadi (Englisia: Journal of Language, Education, and Humanities, 2023)
It is widely believed that L2 learners who have positive attitudes towards the target culture and its people are likely to learn the target language more effectively than those who do not possess such attitudes. As technology continues to be increasingly integrated into language learning, this article aims to explore EFL students' attitudes towards technology acceptance via Virtual Learning Environment (VLE), as well as the potential advantages of VLE in the EFL classroom. A quantitative approach was employed in this study, which involved 30 students from English language education departments at a private university in Indonesia. The students' computer attitudes were assessed using a Likert scale questionnaire with four factors, including affective, perceived usefulness, perceived control, and behavioural intention. The Technology Acceptance Model (TAM) developed by Davis (1989) was utilized as the framework to further examine these factors. The results indicated that the students had a positive attitude towards the Computer Attitude Scale (CAS) factors, which were categorized into affective, perceived usefulness, perceived control, and behavioural intention. The implications of each of these categories in the framework are discussed in relation to behaviourism theory.